PTH-025 Predicting polyp histology – development and validation of an international simple endoscopic classification of small colorectal polyps using the novel i-scan optical enhancement colonoscope. (17th June 2017) - Iacucci, M; Trovato, C; Greenwald, D; Gross, S; Hoffman, A; Jeffrey, L; Lethebe, B; Lowerison, M; Nayor, J; Neumann, H; Sanduleanu, S; Sharma, P; et al.
Abstract : Introduction: The endoscopic accuracy to predict in vivo the histology of small colorectal polyps may facilitate tailored endoscopic treatment. The aims of this study were 1) to develop a simplified endoscopic colorectal polyp classification and 2) to evaluate the performance of the classification to predict polyp histology using i-scan Optical Enhancement (OE) images. Method: Eight endoscopists from Europe and North America with experience in virtual electronic chromoendoscopy participated in the study. A video-library of 21 small colorectal polyps (hyperplastic=7, adenomatous=7, and sessile serrated=7) was assessed. The diagnostic performance of the endoscopists was evaluated according to the histopathology of the polyp. In phase 1 of the study, a new simplified endoscopic classification system for colorectal polyps (Simplified Identification Method for Polyp Labelling during Endoscopy - SIMPLE ) was developed. In phase 2, the accuracy, level of confidence and inter-observer agreement to predict polyp histology before and after a training were evaluated. Univariate and multivariate analysis of the endoscopic features of polyps were performed to determine the strength of endoscopic predictors for adenoma vs. non-adenoma. Results: The SIMPLE classification was consisted of three polyp characteristics: surface, vessel pattern and lesion border. Using the SIMPLE classification, the overall accuracy for prediction of polyp histology was 83.1% (95% CI: 0.77–0.88) before training and improved to 94.0% (95% CI: 0.88–0.97; p=0.002) after training. For polyp diagnosis with high confidence the accuracy before training was 90% (95% CI: 0.83–0.94) and after was 95% (95% CI: 0.89–0.98; p=0.01). The overall sensitivity, specificity, PPV, NPV, of the SIMPLE classification after training were 96.6%, 87.5%, 95.0%, 91.3%, and 94.0%. The inter-observer agreement of polyp histology diagnosis using the SIMPLE classification improved from 0.46 (95% CI: 0.30–0.64) at baseline to 0.66 (95% CI: 0.48–0.82) after training. Univariate analysis showed that the surface and vessel pattern criteria were predictive of an adenoma diagnosis. The odds ratio of adenoma diagnosis were 1.8 (95% CI: 0.7–4.6) when using surface pattern alone and 4.6 (95% CI: 2.3–9.4) when using vessel pattern alone. Conclusion: A new endoscopic SIMPLE classification to predict polyp histology was developed by an international expert consensus group. Using the –i-scan OE system, the new SIMPLE classification was validated and demonstrated a high degree of accuracy for adenoma diagnosis in small polyps, meeting the ASGE PIVI recommendations. Disclosure of Interest: M. Iacucci Conflict with: Pentax, C Trovato: None Declared, D Greenwald: None Declared, S Gross: None Declared, A Hoffman: None Declared, L Jeffrey: None Declared, B Lethebe: None Declared, M Lowerison: None Declared, J Nayor: None Declared, H Neumann: None Declared, S Sanduleanu: None Declared, P Sharma: None Declared, R Kiesslich: None Declared, S Ghosh: None Declared, J Saltzman: None Declared